The Validity of Women's Reports of Family Planning Service Quality in Cambodia and Kenya. Issue 1 (16th March 2021) - Blanc, Ann K.; McCarthy, Katharine J.; Warren, Charlotte; Bajracharya, Ashish; Bellows, Benjamin
Abstract: Population‐based indicators of the coverage of key elements of high‐quality family planning services are tracked via household surveys with female respondents, yet little work has been done to establish their validity. We take advantage of existing data sets from Cambodia and Kenya to compare women's responses at exit interviews following a health facility visit against the observations of a trained third‐party observer during the visit. The results, which treat the observations as the reference standard, show that indicators that measure contraceptive methods received are accurately reported while indicators of whether the woman received her preferred method and whether information was "discussed" or "explained" during counseling are less reliably reported. Studies designed explicitly to assess the validity of family planning questions in household surveys, especially questions in large survey programs critical for monitoring demographic trends and programmatic coverage, are needed.